The Missing Dimension of Modern Education: Values Education - KENAN, SEYFİ (EDAM, 2009)
Modern education today, some argue, easily integrates and adjusts to new technological developments through flexible curricula in the areas where these developments are taking place such as in the field of information technology or in the widespread use of the Internet. However, modern education can be criticized for ignoring or failing to lead societies toward a more humane future in the face of massive social and ecological changes. When it decides to encounter those social problems, the solutions that modern education procures are usually based on a fragmented or reductionist mindset that insulates them from many of the factors generating these problems and their interconnections. This article aims to examine the basic philosophical assumptions that have shaped the modern learning and educational systems and how the split between facts and values occurred. How well is modern education dealing with modern problems - the crisis of family and community, the worsening situation of civic culture and understanding, malpractice in many financial arenas of the world, global warming and dramatic ecological change across the planet, and etc.? Because the animating ideas behind the models of modern education are so strongly shaped by the influence of positivist knowledge and science, they are often inadequate where these issues are concerned because their basic assumptions regarding fundamental and ontological questions which foster students' inner worlds leave no space for the realm of values. I also more broadly discuss the pros and cons of these assumptions as they relate to and deeply influence our lives today.
Keywords: Modern Educational Philosophy; Assumptions of Modern Mindset; Mechanistic-Positivistic Worldviews; Values Education